Implementasi Metode Fun Learning Dalam Meningkatkan Pendidikan Akhlak Santri di Lembaga Pendidikan Al-Qur’an (LPQ) Jami’ul Akbar Desa Klapagading Kecamatan Wangon Kabupaten Banyumas - Nisa Khoerul, Alfi; Umar Fakhruddin, Asef (Jurnal Pendidikan Agama Islam, 2025)
Moral education serves as a reference in nurturing the nation's generation. This is because moral education is very important for students to possess skills and abilities as well as noble character based on the One Supreme God. To support this moral education, it is necessary to have enjoyable learning for students, which can be achieved through the fun learning method to emphasize good moral character for students at the Al-Qur'an Education Institution (LPQ) Jami'ul Akbar in Klapagading Village, Banyumas Regency. This research aims to describe and analyze the implementation of the fun learning method in improving the moral education of students at LPQ Jami'ul Akbar in Klapagading Village, Banyumas Regency. This research employs a descriptive qualitative approach with a case study research type focusing on the students at LPQ Jami'ul Akbar in Klapagading village, Banyumas Regency. Data collection was performed using three methods: observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and conclusion verification. The research results indicate that enjoyable learning methods (fun learning) can be effectively implemented through several stages, namely creating a comfortable, interactive, collaborative, and varied atmosphere. The application of fun learning methods has proven to be able to shape the morals of students at LPQ Jami'ul Akbar, Klapagading Village, Banyumas Regency. This is reflected in the behavior and speech of the students, which demonstrate noble character towards teachers, peers, and parents. The moral education process carried out by the teachers emphasizes understanding and applying Islamic values in daily life, such as being dutiful to parents and teachers, as well as caring for and respecting one another. With a fun approach, the learning process becomes more effective because the students feel comfortable and motivated. Additionally, moral education is also directed towards fostering honest and disciplined attitudes in the daily lives of students. Thus, the fun learning method has proven effective in improving the quality of moral education at LPQ Jami'ul Akbar, through an enjoyable and meaningful approach